EFEKTIFITAS PENGGUNAAN MEDIA GEOGEBRA BERBASIS WEB TERHADAP PEMAHAMAN KONSEP MATEMATIS - Arum Raditaningtyas (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
This study aims to determine the understanding of the concept of students who received Cartesian coordinates material using web-based GeoGebra media and students who received Cartesian coordinates material with WhatsApp Group and to find out whether web-based GeoGebra media was effective in understanding mathematical concepts of Cartesian coordinates material. This type of research is quantitative research using experimental methods. Samples were selected through purposive sampling technique. Analysis of the data used is the Normality Test, Homogeneity Test, and Hypothesis Testing. The results showed that the use of web-based GeoGebra media can help students understand mathematical concepts, as seen from 30 students, the average pretest score was 55,417 and the posttest average was 74,333. While the use of WhatsApp Group does not help students in understanding mathematical concepts, it can be seen from 32 students that the average pretest score is 50.313 and the posttest average is 67.734. Furthermore, from the results of the independent sample t-test the results of the Sig. (2-tailed) of 0.0160.05, then as the basis for decision making in the independent sample t-test, it can be concluded that Ho is rejected and Ha is accepted. Thus, it can be concluded that there are differences in the understanding of the concepts of students who are taught using web-based GeoGebra media and WhatsApp Group material on Cartesian Coordinates. We can see this difference from the average posttest value of the experimental class of 74,333, more than the average posttest value of the control class of 67,734. This means that the use of web-based GeoGebra media is effective in understanding students' mathematical concepts of Cartesian coordinates.